A Mediation Analysis to Detect the Effects of Servant Leadership on Teacher Organizational Citizenship Behavior Using PLS-SEM and IPMA - Shanshan Cheng; Jirui Dong; Hui Sui; Peng Wang; Shu-Jing Wu (SAGE Open)
This study aimed to investigate the relationships between servant leadership (SL), Professional Learning Communities (PLCs), Trust, and Teacher Organizational Citizenship Behavior (OCB). A cross-sectional approach was employed, involving a diverse range of educators. Partial least squares structural equation modeling (PLS-SEM) was used for data analysis. Importance-Performance Map Analysis (IPMA) was also performed. The results indicated that there was no direct significant correlation observed between SL and OCB, suggesting the presence of other moderating or mediating factors. However, it should be noted that SL significantly enhanced Trust, particularly among administrators, thereby leading to an increase in OCB. This highlights the crucial role played by Trust as a mediator. PLCs contribute to the enhancement of OCB and Trust among peers but have a lesser impact within management. Their significance lies in fostering collaboration and support among colleagues. The study confirms that Trust acts as a mediator between PLCs and OCB, emphasizing the importance of social capital in promoting OCB. Recognizing the various contextual factors influencing the effectiveness of SL in educational settings is essential. Leadership strategies need to be tailored to educational environments to cultivate a supportive climate that enhances OCB.